Globalization and communication science - Elizabeth Ferreira (Communicare)
Globalization is an inevitable phenomenon characterized by both integrating and disintegrating forces. This article argues that the outcome of Globalization will be determined by how the global community responds to, and engages in, the process. It suggests that communication scholars can play a role in influencing globalization towards a constructive outcome by directing their research endeavours and theoretical reflection towards finding ways to enhance human development and effective global integration. A conceptualization of globalization for communication science and a number of theoretical approaches which could be used to study the phenomenon from a communication perspective, are proposed. Lastly, suggestions are offered for research contributions that could assist in steering the global system towards a more mature and stable state and the attainment of a higher order of societal consciousness.